Depression Levels Among Bedridden and Non-Bedridden Older Adults in a Residential Care Facility: A Cross-Sectional Comparative Study - Ulfiatun Nafidah; Indari; Riki Ristanto (Jurnal Keperawatan Priority, 2026)
Depression is one of the most common mental health disorders among older adults and is frequently associated with reduced mobility and functional dependence. Older adults who are bedridden often experience limited physical activity, decreased social interaction, and increased dependence on caregivers, all of which may contribute to poorer psychological well-being. However, evidence comparing depression levels between bedridden and non-bedridden older adults living in residential care facilities remains limited, particularly in Indonesia. This study aimed to compare depression levels between bedridden and non-bedridden older adults residing at Husnul Khatimah Residential Care Facility, Malang Regency, Indonesia. A cross-sectional comparative study was conducted involving 110 older adults selected through purposive sampling, consisting of 55 bedridden and 55 non-bedridden participants. Depression levels were assessed using the 15-item Geriatric Depression Scale (GDS-15). Descriptive statistics were used to summarize participant characteristics, and differences in depression levels between the two groups were analyzed using the Mann–Whitney U test. The results demonstrated that bedridden older adults had significantly higher depression scores than non-bedridden older adults (p < 0.001). These findings indicate a significant association between bedridden status and depression levels among older adults. The study highlights the importance of routine psychological assessment, psychosocial support, and interventions aimed at maintaining functional independence to promote the mental well-being of older adults residing in long-term care facilities.